PENGARUH MEDIA PEMBELAJARAN MENGGUNAKAN MACROMEDIA FLASH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK - METTI RAHMAH (Departemen Matematika, 2021)
Learning media is one of the communication tools used in the learning process in the form of lesson materials so that students are more interested in participating in learning activities in order to achieve learning objectives. This study aims to theoretically describe whether the influence of learning media using Macromedia Flash to improve students' mathematical learning outcomes. This type of research is literature study research. This research is a series of activities related to the method of collecting library data, reading and recording, and processing research materials. Data collection techniques used in this study is the study of libraries, namely by collecting data sourced from various journals, books related to objects to be discussed, retrieving library data, reading, recording, and processing research materials with the type of data used is secondary data. After collecting the data then conduct a review of some important terms in the research. Some literature is obtained from various reference sources. An important term defined in this study is the influence of learning media using Macromedia Flash to improve students' mathematical learning outcomes. Then, a journal analysis is conducted based on all the literature that has been obtained by compiling the results of the study. The discussion was conducted by associating the results obtained from journal analysis with existing theories. Then draw conclusions based on the results of the analysis. The last is to make suggestions based on the findings obtained. Based on studies conducted obtained that interactive learning media using Macromedia Flash on learning has an influence to improve learning outcomes. Keywords – Learning Media, Macromedia Flash